Get bigger? Get stronger? Get organised! - Burke, L. (2004)
With half the world needing or wanting to lose weight, it makes a pleasant change to work with athletes who have the opposite goals. Recent work with some of our top swimmers has involved the challenge of achieving a weight increase. One case concerned a swimmer who wanted to increase muscle mass and strength. In another case, the swimmer`s main goal was to stop the loss of skinfolds that usually accompanied periods of heavy training or travel. The author points out a number of practical issues that limit food intake in sport and he gives a number of general guidelines that can be useful to all athletes with high energy needs. Finally useful snacks for the swimmer with high-energy needs are listed.